Characteristics of heating process in microwave applicators with elements in periodic motion. Issue 3 (10th December 2018) - Liao, Yinhong; Wu, Zhiyan; Feng, Xiaoping
Abstract: Moving elements have been widely used in microwave applicators to improve heating uniformity. However, elements in periodic motion can lead to temperature oscillations in the process of heating. In this case, the processed samples are difficult to reach target temperature and the control system may also become unstable. Aiming at overcoming these problems, we investigate the temperature response of the heating process in microwave applicators with elements in periodical motion in this article. By modeling periodical motion as a periodical heat source, the temperature characteristics can be obtained by solving the heat transfer equation with eigenfunction expansions. The results show that the amplitude of temperature oscillations decreases with angular velocity of the element's motion, which is verified by experiments. It means that temperature oscillations can be reduced by increasing the element's velocity, which is helpful to improve the heating performance in microwave applicators.